PENGEMBANGAN MEDIA INTERAKTIF BERBASIS EDUCANDY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA MATERI RAMBU-RAMBU LALU LINTAS KELAS VI SEKOLAH DASAR - Syafira Nur Azizah; Arita Marini; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the difficulties elementary students encounter in comprehending traffic signs, a crucial component of road safety education. While essential, 70% of fourth graders face challenges in interpreting these signs, and traditional teaching methods prove ineffective in capturing their interest. The research investigates the efficacy of Educandy, an interactive game-based learning tool, in improving students' understanding of traffic regulations. Employing a Research and Development (R&D) framework with the ADDIE model, the study engaged 24 fourth-grade students from SDN Karet 01 Jakarta Selatan. Learning outcomes were measured using a pretest-posttest design, alongside student surveys to evaluate engagement and feedback. Results indicated significant progress, with average scores increasing from 74.79 (pretest) to 90.83 (posttest), and an N-Gain score of 63.74%, reflecting moderate effectiveness. Statistical analysis (paired t-test, p < 0.001) validated Educandy's positive influence. The findings suggest that interactive platforms like Educandy can enhance both learning performance and student motivation, though combining them with other instructional strategies is advisable for deeper understanding. This research underscores the value of digital solutions in advancing traffic sign education and promoting road safety awareness among young learners.